PEMBERDAYAAN BADAN USAHA MILIK DESA KERTI DANA DALAM MEWUJUDKAN DESA MANDIRI DI DESA ABANGSONGAN, KINTAMANI - Yasa, I Made Jamin; Amlayasa, Anak Agung Bagus; Soraya, Dewi (JURNAL SEWAKA BHAKTI, 2025)
This community service activity was carried out at BUMDes Kerti Dana in Abangsongan Kintamani Village. Based on the results of initial observations with the Abangsongan village government apparatus, the biggest problem faced is the lack of synergy between the village government, village communities, business actors, and BUMDes in order to develop the village's economic potential. The poor cooperation between the village government, village communities, business actors and BUMDes can be seen from the lack of training and development programs for the community in terms of business management. The solutions given to these problems are (1) Providing counseling related to a more detailed and comprehensive description of the importance of strengthening BUMDes management in order to optimize BUMDes functions for the development of the potential of the village of Abangsongan. (2) Provide education regarding good Bumdes governance. (3) Providing training on basic budget preparation, SOP preparation, business innovation training that will be developed by Bumdes. BUMDes have an important role for the economy of the village government to improve the welfare of its citizens. The results of this PKM activity have a positive impact on increasing the understanding of BUMDes managers. Socialization, training and mentoring activities can increase the understanding and skills of BUMDes managers in the Abangsongan Kintamani village to fulfill administrative obligations, develop SOPs as activity guidelines.